Evaluation of the milk clotting potential and characterization of proteases from Aspergillus sp. and Pleurotus albidus - Nolli, Mariene Marques; Contato, Alex Graça; Brugnari, Tatiane; Buzzo, Ana Júlia dos Reis; Aranha, Guilherme Mauro; Inácio, Fabíola Dorneles; Peralta, Rosane Marina; Souza, Cristina Giatti Marques de (Acta Scientiarum. Technology, 2022)
The study evaluated the production of proteases in solid-state fermentation using wheat bran as a substrate. The best producing isolates were used to obtain crude extract which was evaluated for optimal pH and temperature, thermostability, effect of salts and activity against inhibitors. The studied fungi were Aspergillus sp. 125, Fusarium sp. 132, Fusarium sp. 206, Pleurotus albidus 018 and Pleurotus pulmonarius CCB20. The isolates with better results (Aspergillus sp. and P. albidus), showed protease activity with an optimum pH of 7.0, and an optimum temperature of 50ÂºC with good thermostability between 40 and 50ÂºC. As for salts, the protease activity was inhibited in the presence of ZnSO4, and the activity of the proteases from the crude Aspergillus extract, strongly inhibited by PMSF, indicating the presence of a fraction of serine protease in the extract. The extracts of the two selected isolates showed considerable inhibition by EDTA. The milk clotting activity was 240 U mL-1 for the Aspergillus extract and 153 U mL-1 for the crude P. albidus extract. Proteases are important enzymes widely used in the food industry, including cheese. The data suggest that these fungi have the potential to produce these enzymes for usage in cheese making